2021
DOI: 10.18805/ijar.b-4404
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Beneficiaries and Non-beneficiaries about Scientific Livestock Farming Practices

Abstract: Background: Punjab being a productive state in agriculture and livestock farming, various institutions are actively involved in Self Help Group formation for socio- economic development of low-income group. Rural women are engaged in small-scale entrepreneurship programme with the help of Self Help Groups. The present study was conducted to assess the impact of livestock based Self Help Groups on knowledge level regarding the scientific livestock farming practices among the beneficiaries of Self Help Groups an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The findings demonstrated that recipient farmers had knowledge levels significantly higher than those of non-recipient farmers which may be due to the fact that recipient farmers are having more sources of information under OMM. The findings of the study are in line with the findings of Chaddha et al, (2021) [3] in which he stated that the knowledge index of recipient is more than non-recipients in approx. all four aspect of scientific livestock farming practices.…”
Section: Methodssupporting
confidence: 91%
“…The findings demonstrated that recipient farmers had knowledge levels significantly higher than those of non-recipient farmers which may be due to the fact that recipient farmers are having more sources of information under OMM. The findings of the study are in line with the findings of Chaddha et al, (2021) [3] in which he stated that the knowledge index of recipient is more than non-recipients in approx. all four aspect of scientific livestock farming practices.…”
Section: Methodssupporting
confidence: 91%